THE EFFECT OF PROBLEM–BASED LEARNING AND LEARNING STYLES ON SPEAKING COMPETENCE OF TENTH GRADER IN SMA NEGERI 2 TABANAN - ., MAHAYU SOLINA YUDA; ., PROF. DR. I KETUT SEKEN, M.A.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
Abstract This experimental study aimed at investigating the effect of problem-based learning and learning styles on speaking competence of the tenth graders of SMA Negeri 2 Tabanan in the academic year 2015/2016. This research applied post test only randomized control group design with 2x2 factorial analysis. 157 students were selected as samples through random sampling technique. Data of students’ speaking competence were collected by using performance tests. The students’ competence were scored by using analytical scoring rubric. Meanwhile, students’ learning styles were collected by using questionnaire. The acquired data were analyzed statistically by Two-way ANOVA at 5% significance level. This research discovers: 1) there is a significant difference in speaking competence between students who were taught by problem-based learning strategy and those taught with conventional strategy , 2) there is no effect of interaction between teaching strategy and learning styles on students’ speaking competency 3) there is a significant difference in speaking competence between field dependent students who were taught problem-based learning and those taught with conventional strategy , 4) there is a significant difference between field independent students who were taught by problem-based learning and those taught with conventional strategy. Kata Kunci : problem based learning, learning styles, speaking competence Abstrak Studi eksperimen ini bertujuan untuk menginvestigasi pengaruh pembelajaran berbasis masalah dan gaya belajar terhadap kompetensi berbicara siswa kelas X SMA Negeri 2 Tabanan pada tahun ajaran 2015/2016. Penelitian ini menggunakan post test only randomized group design dengan analisis 2x2 faktorial. 157 siswa dilibatkan sebagai sampel penelitian melalui teknik sample acak. Mereka dipilih dengan teknik sample acak. Data kompetensi berbicara dikumpulkan melalui tes unjuk kerja. Data yang diperoleh dianalisis dengan ANOVA dua jalur. Temuan penelitian ini adalah 1) ada perbedaan yang signifikan antara siswa yang diajar menggunakan strategi pembelajaran berbasis masalah dan yang diajar menggunakan strategi konvensional, 2) tidak ada pengaruh interaksi antara strategi pembelajaran and gaya belajar 3) ada perbedaan yang signifikan antara siswa dengan gaya belajar terikat yang diajar dengan strategi pembelajaran berbasis masalah dan yang diajar menggunakan strategi konvensional, 4) ada perbedaan yang signifikan antara siswa dengan gaya belajar mandiri yang diajar menggunakan strategi pembelajaran berbasis masalah dan yang diajar menggunakan strategi konvensional keyword : pembelajaran berbasis masalah, gaya belajar, kompetensi berbicara